The Internal Microenvironment of the Symbiotic Jellyfish Cassiopea sp. From the Red Sea - Arossa, Silvia; Barozzi, Alan; Callegari, Matteo; Klein, Shannon G.; Parry, Anieka J.; Hung, Shiou-Han; Steckbauer, Alexandra; Aranda, Manuel; Daffonchio, Daniele; Duarte, Carlos M. (Frontiers in Marine Science, 2021)
The characterization of the internal microenvironment of symbiotic marine invertebrates is essential for a better understanding of the symbiosis dynamics. Microalgal symbionts (of the family: Symbiodiniaceae) influence diel fluctuations of in host O2 and pH conditions through their metabolic activities (i.e. photosynthesis and respiration). These variations may play an important role in driving oxygen budgets and energy demands of the holobiont and its responses to climate change. In situ measurements using microsensors were used to resolve the O2 and pH diel fluctuations in the tentacles of non-calcifying cnidarian model species Cassiopea sp. (the “upside-down jellyfish”), which has an obligatory association with Symbiodiniaceae. Before sunrise, the internal O2 and pH levels were substantially lower than those in ambient seawater conditions (minimum average levels: 61.92 ± 5.06 µmol O2 L-1 and 7.93 ± 0.02 pH units, respectively), indicating that conditions within Cassiopea’s tentacles were acidified and hypoxic relative to the surrounding seawater. Measurements performed during the afternoon revealed hyperoxia (maximum average levels: 546.22 ± 16.45 µmol O2 L-1) and internal pH similar to ambient levels (8.61 ± 0.02 pH units). The calculated gross photosynthetic rates of Cassiopea sp. were 0.04 ± 0.013 nmol cm-2 s-1 in individuals collected at night and 0.08 ± 0.02 nmol cm-2 s-1 in individuals collected during the afternoon.